Drug calculations for nurses : a step-by-step approach - Lapham, Robert (Hodder Arnold, 2009)
This handy, introductory guide will enable nurses to perform drug calculations both confidently and competently. It includes worked examples, detailed explanations and graded exercises to promote easy learning.